Tidal volume monitoring by a set of tetrapolar impedance measurements selected from the 16-electrodes arrangement used in electrical impedance tomography (EIT) technique. Calibration equations in a group of healthy males. (May 2016) - Balleza-Ordaz, M.; Alday-Perez, E.; Vargas-Luna, M.; Kashina, S.; Huerta-Franco, M.R.; Torres-González, L.A.; Riu-Costa, P.J.
Abstract: Previously, our research group obtained a set of calibration equations for being used by an electrical impedance tomograph (EIT). All equations transform the impedance changes into a measurable volume signal in a group of healthy males. The performance of EIT, using these equations, was acceptable for respiration monitoring. The EIT impedance changes were obtained from a set of 16-electrodes placed around the thoracic box at level of the sixth intercostal space. Each cycle of impedance measurements is ordered in a matrix (IEITM). Each IEITM's element depicts a configuration of 4-electrodes. Now, our main challenge is to replace the EIT's 16-electrodes by a 4-electrodes configuration. We analyzed the impedance changes obtained from each element and the volume determinations obtained by a pneumotachometer (gold standard) in order to determine the optimal 4-electrodes configuration. For each selected configuration a set of 20 calibration equations were obtained. The best results were obtained by using two 4-electrodes configurations. Both consisting in two adjacent electrodes for current injection and two electrodes for voltage detection. The mean R 2 of the 20 equations determined by the 16-electrodes information, and for the best two 4-electrode configurations were 0.943 ± 0.010, 0.848 ± 0.062 and 0.690 ± 0.122, respectively. The error (%) of volume determinations obtained by the use of 16-electrodes, and by the use of the two best 4-electrode configuration with regarding to the real volume obtained by pneumotachometer were of 15 ± 6%, 16 ± 4% and 43 ± 41%, respectively. The volume differences between the one obtained by the use of 16-electrodes and that for the best 4 electrode configuration were not significant. We conclude that although the determinations of impedance obtained by the best 4-electrode configuration has a lower sensitivity than those obtained by the 16-electrodes, it is possible to measure the respiratory pattern in healthy males.